2016
DOI: 10.1186/s12879-016-1697-6
|View full text |Cite
|
Sign up to set email alerts
|

Faecal carriage of antibiotic resistant Escherichia coli in asymptomatic children and associations with primary care antibiotic prescribing: a systematic review and meta-analysis

Abstract: BackgroundThe faecal reservoir provides optimal conditions for the transmission of resistance genes within and between bacterial species. As key transmitters of infection within communities, children are likely important contributors to endemic community resistance. We sought to determine the prevalence of antibiotic-resistant faecal Escherichia coli from asymptomatic children aged between 0 and 17 years worldwide, and investigate the impact of routinely prescribed primary care antibiotics to that resistance.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 55 publications
(47 reference statements)
2
35
1
3
Order By: Relevance
“…In line with our data, globally, E. coli strains were reported to be highly resistant to the above-mentioned antibiotics, mainly to aminopenicillins [70, 71]. Săndulescu (2016) reported that E. coli showed low resistance to nitrofurantoin, which is in line with the present finding.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our data, globally, E. coli strains were reported to be highly resistant to the above-mentioned antibiotics, mainly to aminopenicillins [70, 71]. Săndulescu (2016) reported that E. coli showed low resistance to nitrofurantoin, which is in line with the present finding.…”
Section: Discussionsupporting
confidence: 92%
“…The studies on effects of antibiotic treatment on intestinal bacteria have mainly revealed an increased level of resistance during and after single courses of treatment [ 8 , 11 ]. The studies show that after antibiotic treatment, the susceptibility either returns to baseline levels shortly after the cessation of therapy [ 11 , 19 ], or there is a prolonged effect even after single courses [ 20 22 ]. Given the fact that systematic, longitudinal studies of the consequences of long-time extensive antibiotic exposure in infants and children are lacking, we have investigated the faecal flora in children with cystic fibrosis (CF) and cancer, two patient groups known to receive much antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Los partidores utilizados para la detección de estos genes bla fueron los siguientes 14,20,21,22 . Para la amplificación de estos genes, se siguieron las siguientes condiciones de temperaturas realizando 35 ciclos de amplificación en Termociclador: …”
Section: Reacción En Cadena De Polimerasa (Pcr) Para Detección De Genunclassified
“…Las Betalactamasas de espectro extendido se ubican dentro de la clasificación de Bush y Jacoby en las categorías 2be, 2ber, 2de y 2der. Siendo una de sus características más importantes, desde el punto de vista epidemiológico, su capacidad de transferirse a través de bacterias de la misma o de diferente especie, por medio de elementos genéticos móviles, que favorece la diseminación de la resistencia bacteriana 14,15 .…”
Section: Introductionunclassified